1968
DOI: 10.1002/j.2164-4918.1968.tb02908.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Success in High School Level Vocational Education Programs: A Review, 1954–1967

Abstract: Over 1,200 correlations reported in 38 studies appearing in the period 1954–1967 are summarized for 10 predictor categories and 11 vocational program areas. For each predictor‐program combination the distribution of correlations is given along with median correlation (r), total number of students involved, number of correlations located, and an index to the relevant studies. Main trends include (a) substantial variation in results from study to study; (b) differences in level of predictor‐criterion r among voc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1971
1971
1978
1978

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Both the similarity scores and the success estimates were to be used in the context of an ongoing vocational guidance program. Previous research has shown that the relationships between antecedent and outcome variables required for data-information conversion are likely to vary from one setting to another (Bennett, Seashore, & Wesman, 1966;Ghiselli, 1966;Passmore, 1968;Prediger, Waple, & Nusbaum, 1968). Hence, the nature of these relationships must be determined for the setting in which data-information conversion procedures are to be used.…”
Section: Figurementioning
confidence: 99%
“…Both the similarity scores and the success estimates were to be used in the context of an ongoing vocational guidance program. Previous research has shown that the relationships between antecedent and outcome variables required for data-information conversion are likely to vary from one setting to another (Bennett, Seashore, & Wesman, 1966;Ghiselli, 1966;Passmore, 1968;Prediger, Waple, & Nusbaum, 1968). Hence, the nature of these relationships must be determined for the setting in which data-information conversion procedures are to be used.…”
Section: Figurementioning
confidence: 99%